Mendidik Pemimpin Masa Depan yang Berkarakter dan Beretika melalui Pendidikan Agama Kristen (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
In The leadership crisis marked by declining moral and ethical integrity in various sectors of life encourages the need for an educational approach that is able to shape future leaders with character and ethics. This study aims to examine in depth the contribution of Christian Religious Education (CRE) in the formation of character and leadership ethics through a qualitative approach based on library research. Data sources were obtained from primary and secondary literature in the form of scientific journals, theological books, and relevant previous research results. The results of the study indicate that Biblical values ​​such as love, justice, humility, and integrity have an important role in shaping transformative Christian leadership. The novelty of this study lies in the interdisciplinary approach that integrates theological, pedagogical, and ethical perspectives in building a contextual and applicable character education model. Therefore, CRE has strategic potential in producing leaders who are not only intellectually capable, but also have a strong moral and spiritual commitment, which is relevant to answering the challenges of leadership in the global and digital era.